Admission of Foreigners during Coronavirus - Zeena Hazim AL-Jubory (الرافدین للحقوق, 2021)
Corona virus is one of the dangerous diseases that greatly affected  the legal relations of the world, especially after the declaration of states to close the borders among them, which caused  severing of  relations and suspension of international interests. This has affected specifically international private relations with regard to foreigners' admission , entry, and residence, in addition to their exit from the countries lands ,and their entries into them. Many countries have forbidden foreigners from entering to their  lands, and some have imposed  restrictions on this entry according to the precautionary measures  that have been taken, as well as expulsion foreigners from the lands of other countries. In this regard the international attitudes varied between ccountries that have observed the humanitarian principles recognized by the constitutions, charters and international agreements, on the one hand, and other countries that have not attained  the required level in treating  foreigners  infected by Coronavirus.